1987
DOI: 10.1063/1.339639
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the 1.35-eV photoluminescence band in InP

Abstract: A commonly observed luminescence band in InP near 1.35 eV has been studied in detail. The dependence of the transition energy on sample temperature and excitation power density indicates the band results from a donor-to-acceptor pair transition involving a donor level with an activation energy of ∼33 meV. Luminescence spectra from samples implanted with Si, Al, or P show that the donors responsible for the band are native defects or complexes that result from radiation damage. These results do not support prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…This large energy shift of the HEB with excitation power is a typical characteristic of a distant deep donor to an acceptor (D-A) transition. 11,12 Moreover, the peak position of the HEB matches the results reported for the Zndiffused InP.…”
Section: Resultssupporting
confidence: 75%
“…This large energy shift of the HEB with excitation power is a typical characteristic of a distant deep donor to an acceptor (D-A) transition. 11,12 Moreover, the peak position of the HEB matches the results reported for the Zndiffused InP.…”
Section: Resultssupporting
confidence: 75%
“…The luminescence peak at 1.416 eV energy is due to transition between band states and shallow donors [17][18][19][20][21] and is very close to the band gap energy of InP. The peak at 1.380 eV is thought to be a transition from a shallow donor to a shallow acceptor pair, and band to acceptor [20][21][22][23], and the peak at 1.337 eV is a phonon replica that appears at 43 meV lower energy than the 1.380 eV peak [22,23]. As also seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…With the reduction of indium in the InP films (for stoichiometric and phosphorous rich films), indium vacancies (V In ) and/or phosphorous interstitials acting as shallow acceptors would participate in the transition resulting in the reduction of the intensity of the transition at ∼1.35 eV. It may be noted here that Kim et al [33] attributed this peak to DA pair transition involving a relatively deep donor level (∼33 meV) appearing due to native defects or related complexes. Temkin et al [34] also indicated the presence of such donor like phosphorous vacancies, acceptor like indium vacancy and P interstitials in explaining the PL studies of their system.…”
Section: Photoluminescence Studiesmentioning
confidence: 87%